Perbandingan hasil belajar siswa menggunakan e-modul berbasis CTL dengan buku teks fisika pada materi hukum newton gravitasi dan usaha energi kelas X SMAN 2 Padang - Nadia Ramadhanty; Desnita Desnita; Asrizal Asrizal; Yenni Darvina (Universitas Negeri Padang, 2020)
The 2013 curriculum demands the use of ICT-based media and diverse learning resources. Everyday events, textbooks, teachers, modules, worksheets, videos, and other learning resources can be chosen by the teacher as a learning resource. The fact found in the field, that the learning resources used are textbooks and do not use everyday contexts. E-modules can represent ICT and independent learning materials. The purpose of this study was to determine differences in student learning outcomes using the E-module based CTL with physics textbooks at SMAN 2 Padang. This type of research used is a quasi-experimental research design with Randomized Posstest Only Control Group Design research. The population in this study were all students of Class X Science in SMA Negeri 2 Padang who were registered in the 2019/2020 school year. Sampling using a purposive sampling technique. The sample in this study there are 2 classes, namely experimental class I and experimental class II with a total of 36 students each. Data in this study were analyzed using descriptive statistics. By conducting a normality test and a homogeneity test it is evident that the data of both groups are normally distributed and both are homogeneous. Tests of similarity of two averages for all aspects of learning outcomes, carried out at the real level of 0.05 and degrees of freedom to 70. The results of cognitive calculation tcount = 3.8966 while ttable = 1.9900, for affective aspects tcount = 4.694 and ttable = 1.9900 and for psychomotor aspects thitung = 2.9056 while table = 1.9900. From the three aspects obtained t count> t table. Based on the results of the study it can be concluded, that the learning outcomes of students taught using E-modules based on CTL are better than students who are taught using textbooks.